MODEL PEMBELAJARAN CONNECTING, ORGANIZING, REFLECTING, DAN EXTENDING (CORE) UNTUK MENINGKATKAN KREATIVITAS SISWA DI SMK MUHAMMADIYAH 13 SIBOLGA - Iwan Setiawan Nasution; Benny Sofyan Samosir (Universitas Muhammadiyah Tapanuli Selatan, 2018)
The problem in this research is the lack of ability of creativity in students. To fix the issue, on the research learning model applied to Connecting, Organizing, Reflecting, and Extending (CORE). Research objectives for the enhancement of creativity and learning activities of students in learning mathematics through the application of the model of learning a CORE class XI Accounting SMK Muhammadiyah 13 Sibolga. This type of research is research action class. Where the subject of this research is the grade XI Accounting SMK Muhammadiyah 13 Siboga consisting of 36 students. While the techniques and data-collecting instruments namely observation and tests. Research results can be seen from the students ' creativity ability test on cycle I with a percentage of 53% in cycle II an increase in the percentage of 82% with an increase of 29%. Activity levels of students against mathematics increases, it is retrieved from 63% percentage of the cycle I, and 82% in cycle II increased by 18%. The ability of the teacher to manage learning percentage of 72% in cycle I and 94% in cycle II, with an increase of 23%. Based on the results of this study, it can be concluded that the model Connecting, Organizing and Extending (CORE) can increase creativity in learning mathematics processed XI accounting SMK Muhammadiyah 13 Sibolga.